1994
DOI: 10.1007/bf00198565
|View full text |Cite
|
Sign up to set email alerts
|

Concentrations of inorganic and organic solutes in extracts from individual epidermal, mesophyll and bundle-sheath cells of barley leaves

Abstract: Abstract. The distribution of solutes between epidermal, mesophyll and bundle-sheath cells in barley (Hordeum vulgare L. cv. Klaxon) leaves was studied by analysing extracts obtained from single cells with a modified pressure probe. Activity of the cytoplasmic marker enzyme, malate dehydrogenase, revealed that epidermal cell extracts were completely vacuolar in origin, but extracts from mesophyll cells also contained cytoplasmic constituents. The extracts were analysed for osmolality and the concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
81
0

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(89 citation statements)
references
References 26 publications
8
81
0
Order By: Relevance
“…6 a), the total concentration of sugars was c. 50-70 mM for mesophyll and bundle sheath cells. In the epidermal cells the sum of the sugar concentration was < 10 mM, in good agreement with the data obtained by Fricke et al (1994) by the same technique and with the results of Dietz et al (1994) obtained using isolated epidermal protoplasts. In both mesophyll and bundle sheath cells, concentration of sucrose was about 30-50 mM at the beginning of the light period, when the fructose concentration was very close to that of sucrose in mesophyll cells.…”
Section: Analysis Of Individual Mesophyll Bundle Sheath and Epidermasupporting
confidence: 89%
“…6 a), the total concentration of sugars was c. 50-70 mM for mesophyll and bundle sheath cells. In the epidermal cells the sum of the sugar concentration was < 10 mM, in good agreement with the data obtained by Fricke et al (1994) by the same technique and with the results of Dietz et al (1994) obtained using isolated epidermal protoplasts. In both mesophyll and bundle sheath cells, concentration of sucrose was about 30-50 mM at the beginning of the light period, when the fructose concentration was very close to that of sucrose in mesophyll cells.…”
Section: Analysis Of Individual Mesophyll Bundle Sheath and Epidermasupporting
confidence: 89%
“…The epidermis of barley leaves could be an intermediary storage compartment for sugars and contain as much as 5-15 % of the leaf's glucose and fructose (Dietz, Hollenbach & Hellwege, 1994). However, in other studies the epidemis was shown to contain extremely low concentrations of sugars, c. 2 mM (Fricke, Leigh & Tomos, 1994).…”
Section: Introductionmentioning
confidence: 94%
“…Differential compartmentation of inorganic ions between the mesophyll and the upper and lower epidermis of leaves has been reported for a number of monocotyledonous and dicotyledonous species (Karley et al, 2000). Also, sugars and amino acids are not evenly distributed in barley leaves, with concentrations being much lower in the epidermis (Dietz et al, 1994;Fricke et al, 1994). Unfortunately, in these very detailed studies, the techniques used for derivatization and detection of amino acids were not suitable for analyzing Pro concentrations.…”
Section: Complementary Expression Indicates Different Roles For Atpromentioning
confidence: 99%